PENGEMBANGAN MATERI PERILAKU ASERTIF SISWA SMA/SEDERAJAT - Raja Ruari Sandiky; Zulfan Saam; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Assertive behavior is very important for student, because if student doesn’t have any skill for assertive behavior. More ove not being in assertive behavior, this student will lose the righs as individual and disposed to become the individual who doesn’t has freedom and will always be in another person dominance. Therefor,this service material is necessary expand to become a material about the assertive behavior of Senior High School students, whichis hoped to be used by guidance and counseling teachers to be taught to students. The purpose of this research are 1) the compolation of the assertive behavior of senior high school’s students material which observed by the systematic clarity, image support, comprehensiveness, innovation, games/video. 2) to determine the quality of the assertive behavior of senior high schools student. This material is compiled by using Research ang Development method. Then being tried to students with 4 hours lesson time allocation (4 x 45). This material is valid by the first and second counselor lecturer, guidance and counseling teachers, and 25 students of state senior high school 5 pekanbaru. The material consist of the definition of assertive, the characteristic of assertive behavior, assertive behavior aspect, the factors which influenced by assertive behavior, the function of assertive behavior and the effort increase assertive behavior. The result of this material is a compilation module of assertive behavior senior high school students with the material quality in “Good” category with 4,10 score for all marking.Keywords : Guidance And Counseling, Assertive Behavior,Senior High School